Le geste de l'écrit :. - Vanlatum, Anne (Sars-Poteries : Musée-atelier du verre à Sars-Poteries, 2011)
Alechinsky, Pierre ; Bloch, Pierrette ; Divry, Jean ; Dotremont, Christian ; Koch, Gérard ; Licata, Riccardo ; Lynch, David ; Massoudy, Hassan ; Michaux, Henri ; Mukaide, Keiko ; Perrin&Perrin ; Umbdenstock, Jean-Pierre
boek